Pulmonary Artery Catheter Thrombus in a Patient With Essential Thrombocytosis: A Case Report. Issue 8 (15th April 2019) - Lu, Shu Y.; Shelton, Kenneth T.; Fitzsimons, Michael G.
Abstract : Essential thrombocytosis (ET) is a rare chronic myeloproliferative disorder characterized by elevated platelet counts. The management of patients with ET undergoing coronary artery bypass graft remains unclear. Often, patients who are deemed "high risk" for thrombotic events receive cytoreductive therapy before surgery, while patients deemed "low risk" do not receive cytoreductive therapy. Here, we present a case of a patient with ET with only a mild elevation in platelets deemed "low risk" for thrombotic complications who was found to have a small intracardiac thrombus around the pulmonary artery catheter before initiation of cardiopulmonary bypass.